Analisis kriteria mutu tujuan jangka panjang dan pengaruhnya terhadap keputusan manajerial: kasus pada bank syariah indonesia - Nurahmani, Marsheila Fithri Aisyah (Maliki Interdisciplinary Journal, 2025)
En Long-term goals serve as the primary guideline in strategic management because they determine the direction of organizational policy. This article aims to assess the quality of Bank Syariah Indonesia's (BSI) long-term goals by referring to seven main criteria: acceptable, flexible, meaurable, motivating, suitable, understandable, and achievable. It also analyzes their influence on the managerial decision-making process. The approach applied is a conceptual method with theoretical analysis and literature study on strategic management and BSI's performance reports. The results show that BSI has met most of the main criteria in terms of acceptability, meaurability, suitability, and achievability, as evidenced by the alignment between its vision, performance indicators, and the principles of maqashid sharia. However, flexibility and understanding still require improvement in adapting to changes in the digital industry and internal communication. Conceptually, the quality of ideal long-term goals increases the efficiency of decision-making at the strategic, tactical, and operational levels. This research is expected to contribute to strengthening the strategic planning of Islamic financial institutions and serve as a foundation for further empirical research.